Preparation of fine-grain aluminum alloy by spinning method and its corrosion resistance test - Yu, Yang (Journal of physics. Conference series, 2024)
Due to the lack of shear resistance, the implanted materials in the aluminum alloy will lead to obvious wear. The emergence of fine-grained aluminum alloy materials can perfectly solve the above problems. Therefore, in this paper, the fine-grain aluminum alloy material is prepared by the spinning method, and the corrosion resistance test is carried out. The experimental results show that there is no significant difference in weight loss and surface morphology between aluminum alloy and fine-grain aluminum alloy immersed in normal saline and D-Hand’s solution for 30 days. The experimental results show that the fine-grained aluminum alloy has the basic conditions for in vivo implantation, which lays a foundation for the development of a new generation of in vivo implantation materials.